Kerja Sama Guru Dan Orang Tua Pada Pembelajaran Tahfid Quran Bagi Anak Usia Dini - Ahmad Zain Sarnoto; Busthomi Ibrohim; Taufik Nugroho (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2021)
When the child is obliged to memorize the verses of the Qur'an in front of the teacher. Some young children still find it difficult to master and need adults to help deal with this problem. Meanwhile, RA Bait Qur 'any at-Tafkir views that the process cannot run only in schools but requires optimizing the relationship with parental education. This case study research explores and further analyzes the pattern of relationships developed in RA in establishing relationships with parents in order to strengthen the memorization of their students. In addition to holding regular meetings through the walidain madrasa, RA Bait Qur 'any at-Tafkir also applies home learning. All of these activities relate to the position and benefits of parents to carry out the Quran memorization program at RA at-Tafkir.